Profil Keterampilan Argumentasi Siswa Kelas X dan XI MIPA di SMA Batik 1 Surakarta pada Materi Keanekaragaman Hayati - Nurul Faiqoh; Nadhirotul Khasanah; Lia Puji Astuti; Riski Prayitno; Baskoro Adi Prayitno (Jurnal Pendidikan Biologi, 2018)
The research aims to know the argumentation skill profile and the difference of students' argumentation skill between 10th MS (Match and Science) and 11th MS in Batik 1 Senior High School of Surakarta on Biodiversity material. The type of research is descriptive quantitative using survey method. Population research is all students or 400 students of class 10th and 11th MS in SMA Batik 1 Surakarta. Sampling technique using stratified proportional random sampling. The instrument to measure the skills of the user is using essay handbooks. Analysis of argumentability was using Toulmin's Argumentation Pattern (TAP). The data were analyzed using quantitative descriptive. The results showed the quality of the students' argumentation in one of the Private High School Surakarta in sufficient category. Percentage of achievement of each indicator is 68% claim, 60% warrant, 53% data, 45% s backing and 0% rebuttal. The result of t-test got sig. (2-tailed) about 0.002. therefore we can conclude that argumentation skill of 10th and 11th MS in SMA Batik 1 Surakarta have significant differences of class X and XI argumentation skill shows a significant differences, although the argumentation skill quality of both cluster class is enough.